Review of the national health promotion strategy 2004 (Department of Health and Children, 2004)
The review focuses on the new national health strategy implemented in Ireland in 2004. Written for professional public.
Keywords: Government Programs; vládní programy; hodnocení programu; veřejné zdravotnictví; podpora zdraví; zdravotní politika; Health Policy; Ireland; Irsko; Health Promotion; Program Evaluation; politologie, politika, zdravotní politika; reforma zdravotní péče; Health Care Reform